Multiple magneto-phonon resonances in graphene. (27th January 2016) - Basko, D M; Leszczynski, P; Faugeras, C; Binder, J; Nicolet, A A L; Kossacki, P; Orlita, M; Potemski, M
Abstract: Our low-temperature magneto-Raman scattering measurements performed on graphene-like locations on the surface of bulk graphite, carries the energyite reveal a new series of magneto-phonon resonances involving both K point and Γ point phonons. These are resonances between a purely electronic excitation, an electronic excitation accompanied by one phonon, and a two-phonon excitation. In particular, we observe the resonant splitting of three crossing excitation branches. We give a detailed theoretical analysis of these multi-excitation resonances. Our results highlight the role of combined excitations and the importance of multi-phonon processes (from both K and Γ points) for the relaxation of hot carriers in graphene.